Experimental and analytical investigation of high performance concrete beams reinforced with hybrid bars and polyvinyl alcohol fibers. (30th October 2020) - Said, Mohamed; Mustafa, T.S.; Shanour, Ali S.; Khalil, Mostafa M.
Highlights: Discussion of the performance of concrete beams containing ECC. PVA fibers enhanced the cracking load, ultimate capacity. Hybrid bars exhibited an improvement in the stiffness of the concrete beams. The inclusion of hybrid bars delayed the appearance of the first crack. PVA exhibits an improvement in the ductility factor and strain ductility. Nominal flexural strength and flexural rigidity were assessed. Abstract: This paper investigates the flexural performance of engineered cementitious composite (ECC) concrete beams reinforced with innovative hybrid bars. Hybrid bars combine the advantages of both FRP and steel bars in enhancing the ultimate strength, ductility, and corrosion resistance compared with pure FRP or steel bars. Twelve half-scale ECC-concrete beams were tested to study the flexure behaviour under four-points loading test using polyvinyl alcohol (PVA) ECC fibers. Polyvinyl alcohol (PVA) fibers were used in the ECC mix for this purpose. The experimental variables are the hybrid reinforcement ratios (0.85%, 1.26%, and 1.7%), PVA fiber ratio (0.0%, 0.75%, and 1.5%) and hybrid schemes (hybrid and GFRP bars). The test results showed significant enhancement in the capacity of ECC concrete beams reinforced with hybrid bars or hybrid schemes. The achieved enhancements are 12% and 27% for PVA ratio of 0.75% and 1.5% respectively. In the presence of PVA fibers, the ultimate strain of the bars is higher than that registered in the absence of PVA fibers. Non-linear finite element analysis (NLFEA) was carried out to validate the experimental results. The NLFEA is adequately simulating the experimental results. Nominal flexural strength and flexural rigidity were assessed with the experimental test results and validated with 77 available ECC-concrete beams from the literature. The validation proved that the assessments of the nominal flexural strength and flexural rigidity are performed well in the prediction. Finally, a comprehensive sensitivity study is conducted to illustrate the effect of PVA-ECC on the flexural rigidity of the beams. The experimental evidence presented in the current study demonstrates the feasibility and plausible future of the novel hybrid bars and PVA fibers especially for marine and waterfront concrete structures.